Formes et effets de l’autonomie au travail : le cas des aides à domicile dans la construction de leurs propres plannings - Laëtitia Flamard; Xavier Marchand (Activités)
Autonomy has long been considered an individual objective of operators, but collective autonomy is increasingly becoming an objective of managers and directors in order to deal with the challenges of competitiveness. Organisations centred on the principle of autonomy are developing in the home help sector, especially through the activity of staff scheduling, i.e. the design of work schedules, the scope most often allowed for the development of home worker autonomy. The article proposes a comparative analysis of three feedbacks on the implementation of so-called autonomous teams in this sector. Together with an analysis of activity and empowerment processes, the aim of this article is to anchor the issue of autonomy in work practices - to analyse how, here in the field of scheduling, activities and strategies develop on the basis of the resources made available.In this context, home helpers construct a collective and negotiated schedule. Yet this articulation work does not always suffice to design acceptable and accepted schedules. The contrast between the results obtained in different organisations shows that autonomy is by no means a foregone conclusion and must be built dynamically and within a favourable technical and social environment, in which managers have an essential role to play, even though they themselves are affected by a change in their role and their managerial practices.